A Review on Functions of Rakt Dhatu and Prana Vayu to Establish Lung Function Capacity - Shamrao Patil, Dr. Vishal; Bhalsing, Dr. (Mrs.) Manisha V. (International Journal of Innovative Research in Medical Science, 2018)
Lung function tests are useful in assessing the functional status of Respiratory system in both in physiological as well as pathological conditions. These are based on the measurement of volume of air breathed in and out in quite breathing & forced breathing. Air in lungs is classified in to two divisions’ lung volumes & lung capacities. Lung Capacities are the combination of two or more lung volumes. The concept of Rakt Dhatu & Vayu is important in case of respiration because Charaka says that pure blood provides the person with strength, luster & happy life because vital breath follows blood. It represents mechanism of oxygenated & deoxygenated blood & its relation with functioning capacity of Lungs. So In this article attempt has been made to review concepts regarding functions of Rakt Dhatu & Vayu to Establish Lung Function Capacity.